Maintaining the close-to-critical state of thorium fuel core of hybrid reactor operated under control by D-T fusion neutron flux; Nuclear Engineering and Technology; Vol. 53, iss. 6 - Bedenko S. V. Sergey Vladimirovich; Arzhannikov A. V. Andrey Vasilyevich; Lutsik I. O. Igor Olegovich; Prikhodko V. V. Vadim Vadimovich; Shmakov V. N. Vladimir Mikhaylovich; Modestov D. G. Dmitry Gennadjevich; Karengin A. G. Aleksandr Grigorievich; Shamanin I. V. Igor Vladimirovich (2021, 2021)
Title screen